Simultaneous Determination of Five Chromones of Radix Saposhnikoviae Extract in Rat Plasma by UPLC-MS/MS: Application to a Comparative Pharmacokinetic Study in Normal and Febrile Rats - Li Meng; Hui Gao; Bin Chen; Peng-peng Liu; Guo-shun Shan; Fan Zhang; Tian-zhu Jia (Journal of Analytical Methods in Chemistry)
A rapid and sensitive quantitative analytical method was established for the simultaneous determination of five chromones (prim-O-glucosylcimifugin, cimifugin, 4′-O-β-D-glucosyl-5-O-methylvisamminol, 5-O-methylvisammiol, and sec-o-glucosylhamaudol) in the plasma of RS-treated rats for the first time using ultra performance liquid chromatography- (UPLC-) tandem mass spectrometry. The Waters Acquity UPLC BEH C18 (50 mm × 2.1 mm, 1.7 μm) was used as the chromatographic column, 0.1% formic acid water and 0.1% formic acid acetonitrile comprised the mobile phases, and all samples were determined under positive ion mode. The results showed that all analytes had good linearity (r>0.9902), between-day and within-day precisions less than 15%, accuracy between −5.50% and 5.53%, and extraction recovery between 88.26% and 97.65%. Both the matrix effect and stability met the requirements. This method was successfully applied for the comparative pharmacokinetics of five active components of RS in normal and febrile rats. The results showed that the pharmacokinetic behavior of RS extract significantly differed between the two types of rats.